Synthesis of polymer brushes from salen ligand/silica and its application as catalyst for the hydrolytic kinetic resolution of epichlorohydrin - Son Nam, Phan Thanh; Christopher, W. Jones (Vietnam Journal of Chemistry, 2014)
A new approach to polymer brushes based on the surface-initiated atom transfer radical polymerization (ATRP) of functionalized salen monomer and styrene on nonporous silica was demonstrated. The hybrid material was characterized using FT-IR, TGA, DSC, 29Si and 13C CP-MAS NMR techniques. The corresponding cobalt complex of the polymer brusches was used as a highly efficient recyclable catalyst for the hydrolytic kinetic resolution of racemic mixture of epichlorohydrin. The reaction was carried out under solvent-free condition at room temperature in the presence of 0.5 mol% of cobalt, with enantiomeric excess (ee) of higher than 99% and a conversion of 55% being achieved after 1.5 hours. While formally heterogeneous, the hybrid cobalt(salen) catalyst could offer the high enantioselectivity and activity of homogeneous catalysts due to the soluble polymer chains, and the advantages of facile separation and recyling of heterogeneous catalysts.